Assessment of the heavy metal pollution and health risks of rice cultivated in Hainan Island, China. Issue 1 (3rd April 2021) - Zang, Zhenfeng; Li, Yonghua; Liu, Suhua; Li, Hairong; Hao, Zhe; Xu, Yuefeng
Abstract: This study aims to evaluate the pollution characteristics of rice cultivated in Hainan Island and assess the health risks to humans through consuming rice. Results indicate that except lead (Pb), the mean contents of other heavy metals in rice are all within the standard limits. According to the spatial distribution and pollution indices of heavy metals, rice is severely polluted with Pb and the contaminated areas are mainly distributed in the west and northeast regions of Hainan Island. Analyses on the non-carcinogenic risks indicate that the target hazard quotients (THQs) of individual heavy metals are significantly different in the study area, and the THQs of chromium (Cr) and arsenic (As) are above 1, implying that people consuming the local rice are susceptible to health risks caused by Cr or As, which is significantly different form the results of single pollution indices of Cr, As, and Pb. This result is mainly related to the original concentrations and reference oral dose for ingesting (RfDing ) of Cr, As, and Pb. As for the assessment of carcinogenic risk, it demonstrates that Cr and As may have adverse effects on inhabitants consuming local rice.